L’EVOLUTION DES PARA METRES PHYSICOCHIMIQUES PENDANT LA CROISSANCE DE LA SPIRULINE - Bara Soundous; Khelaldjiya Manel (My University, 2022)
Spirulina is a blue- green algae, microscopic (10 to 12 μm in diameter), mobile and helical in shape. Known for its valuable nutritional benefits and special benefits for humans. Spirulina grows naturally in some of the warm alkaline lakes of Chad and Mexico and photosynthesizes like plants. The experiment was carried out under experimental conditions in which the temperature is fixed at 29° C., with an acidity varying between 9 and 10, under constant stirring, a medium rich in nutrients (Hiri's medium) is used. Two types of distilled water and tap water are also used for cultivation. This study is conducted to evaluate the growth of spirulina, the work was devoted to the study of "Arthrospira platensis", and the objective of this work is to study the chemical and physical changes during the growth of spirulina under appropriate experimental conditions. ------------------------------------------------------------------------------------------------------------- سبيرولينا هي طحالب خضراء مزرقة، مجهرية (قطرها 10 إلى 12 ميكرومتر)، متحركة وحلزونية الشكل. معروف بفوائده الغذائية القيمة وفوائده الخاصة للإنسان. تنمو السبيرولينا بشكل طبيعي في بعض البحيرات القلوية الدافئة في تشاد والمكسيك وتقوم بعملية التمثيل الضوئي مثل النباتات. أجريت التجربة في ظل ظروف تجريبية تكون فيها درجة الحرارة ثابتة عند درجة حرارة 29 درجة مئوية وحموضة تتراوح بين 9 و 10 مع التحريك المستمر . يتم استخدام غني بالمواد المغذية (وسط هيري). كما يتم استخدام نوعين من الماء المقطر وماء الصنبور في الزراعة. أجريت هذه الدراسة لتقييم نمو السبيرولينا، وخصص العمل للدراسة "Arthrospira Platensis"، والهدف من هذا العمل هو دراسة التغيرات الكيميائية والفيزيائية أثناء نمو السبيرولينا تحت الظروف التجريبية المناسبة. ------------------------------------------------------------------------------------------------------------- La spiruline est une algue bleu-vert, microscopique (10 à 12 µm de diamètre), mobile et de forme hélicoïdale. Connu pour ses précieux bienfaits nutritionnels et ses bienfaits particuliers pour l’homme. La spiruline pousse naturellement dans certains des lacs chauds et alcalins du Tchad et du Mexique et effectue la photosynthèse comme les plantes. L'expérience a été réalisée dans des conditions expérimentales dans lesquelles la température est fixée à 29°C, avec une acidité variant entre 9 et 10, sous agitation constante, un milieu riche en nutriments (milieu de Hiri) est utilisé. Deux types d’eau distillée et d’eau du robinet sont également utilisés pour la culture. Cette étude est menée pour évaluer la croissance de la spiruline, les travaux ont été consacrés à l'étude de "Arthrospira platensis", et l'objectif de ce travail est d'étudier les modifications chimiques et physiques au cours de la croissance de la spiruline dans des conditions expérimentales appropriées.